Sadarbība visa pamatā - Ausma Špona - Puķīte, Santa (LU Muzejs, 2024)
Raksts par Latvijas Universitātes (LU) emeritēto profesori Dr. habil. paed. Ausmu Šponu, par viņas bērnības gadiem, skolas laiku un mūža ieguldījumu pedagoģijā un augstākajā izglītībā. Raksts tapis par godu profesores 90 gadu jubilejai.

An article about the University of Latvia (LU) emeritus professor Dr. habil. paed. Ausma Špona, about her childhood years, school years and lifelong contribution to pedagogy and higher education. The article was written in honor of the professor's 90th anniversary.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Pedagoģija; Izglītība; LU vēsture; LU Muzejs; Pedagogy; Education